Predicting Impacts of Offshore Monoculture Farm Expansion in Ultra-Oligotrophic Waters of the Levantine Basin - Livne, Leigh; Grossowicz, Michal; Tchernov, Dan; Ayalon, Ofira (Frontiers in Marine Science, 2020)
The aim of this brief research report was to define the consequential shifts in biomass and trophic structure of an ecosystem surrounding an offshore monoculture fish farm in Israel. It attempts to clarify the impact of the industry expansion and input of artificial fish pellets on functional group biomasses. We account for the direct addition of artificial food pellets, as well as metabolic wastes from the caged fish in a mass-balance food web model (Ecopath), as well as the temporal expansion of the farm’s production capacity to 21,000 t over a 30-year period (Ecosim). In the former static mass-balance model of the food web, the addition of the fish cages at its current production size of 1000 t does not adversely affect the system, and trophic energy transfer is still dependent on primary production versus the detrital pathway. The model suggests a semi-stable ecosystem with low trophic interactions. With time, the increase in fish farming at the site is characterised by an increase of all functional group biomasses at the site over the 30-year period. The accumulation in detritus most notably correlates to greater biomass for all benthic functional niches and their secondary consumers. It is, therefore, apt to develop an indicator species list to indicate negative site disturbance. In summary, the sediment column condition will be the indicator for ecosystem stability, as well as large predator attraction to the cages from the input of artificial pellets and the accumulation of dead fish at the cage bottom.